ASEAN and EAEU: Cooperation Problems and Prospects - Irina Vladimirovna Zeleneva; Elizaveta Andreevna Kontsova (Управленческое консультирование)
The article focuses on the problems and prospects of the collaboration between the Association of Southeast Asian Nations and the Eurasian Economic Union. Present international issues encourage the active collaboration between countries in multiple spheres. Integration unions are logical for they bring mutual economic benefits. Globalization deepens ties between countries, intensifies interdependence and complementarity among them. Even while a crisis occurs in one particular country it may affect the whole world community. Thus countries initiate and strengthen integration, and new strong regional structures are being built to achieve economic and political security with better life conditions. Progressive tendency towards regionalization has a double effect. In one way, it reinforces globalization. In another, it fosters isolation of integration unions from the world market and increases their independence from the external demand. In turn, this allows a higher resistance to emerging crises and economic shocks by creating an «airbag», in a manner of speaking, to protect a particular regional integration union from the global economy. A good example of regional groupings created with this aim in mind is the Association of Southeast Asian Nations and the Eurasian Economic Union. Joining the regionalization also has a benefit of relative independence from the dominant actors of the world economy and politics, such as the US, the EU, China. Asian countries, and Russia is in some measure among them, have built plenty of integration alliances within the last 60 years. Fairly often a country associates with more than one of such alliances. For instance, Indonesia and Russia are united within APEC, while Indonesia is a member of ASEAN, and Russia is a member of EAEU. Such interactions are deeply intertwining in a sophisticated relation hierarchy in Asia, that brings expenditures. This encourages countries to harmonize trade procedures and laws, that are of vital importance in cooperation between the unions. However both ASEAN and EAEU have a range of controversies between members, that impede further integration, as well as negatively affect relations with external partners. Hence, the perspectives of cooperation between two organizations are limited so far, but there are prospects in ASEANRussia and EAEU-Vietnam cooperation.